'Rideaux rouges': The Scene of Ideology and the Closure of Representation (Matter and Theatre in Althusser and Derrida). Issue 1 (May 2022) - Clément Mercier, Thomas
Abstract : As they make their way through Louis Althusser's and Jacques Derrida's texts, readers will cross innumerable curtains – 'the words and things', as Derrida says, as many fabrics of traces. These curtains open onto a multiplicity of scenes and mises en scène, performances, roles, rituals, actors, plays – thus unfolding the space of a certain theatricality. This essay traces Althusser's and Derrida's respective deployments of the theatrical motif. In his theoretical writings, Althusser's theatrical dispositive aims to designate the practical and material dimension of the scenes of ideology, materially enacted through roleplays, performances, acts, or discourses. At the horizon: a scientific discourse on ideology or, later, a strategic intervention in the class struggle. This scientific and/or strategic orientation echoes Althusser's definition of materialism: 'no more storytelling'. But Derrida's 'closure of representation' reminds us that there's no presence – even the most 'material' – no 'truth' or 'correctness' – in theoretical or strategic terms – without effects of re-presentation, differential repetition, narrative reconstruction: theatricality and materiality suppose a force of resistance, a secret heterogeneity, curtain foldings. Hence the irreducible necessity of reading, storytelling, transformative interpretation. What are the implications for thinking inheritance and debt – for example, the one binding Althusser and Derrida, and us to them?